Scavenging neurotoxic aldehydes using lysine carbon dots. Issue 5 (7th February 2023) - Bloch, Daniel Nir; Sandre, Michele; Ben Zichri, Shani; Masato, Anna; Kolusheva, Sofiya; Bubacco, Luigi; Jelinek, Raz
Abstract : Reactive neurotoxic aldheyde DOPAL, enzymatically produced from dopamine in cells and tissues, is associated with adverse physiological effects. Lysine-C-dots inhibit DOPAL-induced α-synuclein oligomerization and cytotoxicity. Abstract : Reactive aldehydes generated in cells and tissues are associated with adverse physiological effects. Dihydroxyphenylacetaldehyde (DOPAL), the biogenic aldehyde enzymatically produced from dopamine, is cytotoxic, generates reactive oxygen species, and triggers aggregation of proteins such as α-synuclein implicated in Parkinson's disease. Here, we demonstrate that carbon dots (C-dots) prepared from lysine as the carbonaceous precursor bind DOPAL molecules through interactions between the aldehyde units and amine residues on the C-dot surface. A set of biophysical and in vitro experiments attests to attenuation of the adverse biological activity of DOPAL. In particular, we show that the lysine-C-dots inhibit DOPAL-induced α-synuclein oligomerization and cytotoxicity. This work underlines the potential of lysine-C-dots as an effective therapeutic vehicle for aldehyde scavenging.